Pursuit-evasion differential game with many inertial players - Ibragimov, Gafurjan I.; Salimi, Mehdi (Hindawi Publishing Corporation, 2009)
We consider pursuit-evasion differential game of countable number inertial players in Hilbert space with integral constraints on the control functions of players. Duration of the game is fixed. The payoff functional is the greatest lower bound of distances between the pursuers and evader when the game is terminated. The pursuers try to minimize the functional, and the evader tries to maximize it. In this paper, we find the value of the game and construct optimal strategies of the players.